Industry expertise of audit committee chairman and audit report LAG: Evidence from Malaysia - Karamah Banjary, Anas Rasheed (2019)
Timeliness is considered as one of the important aspects of financial information that could be beneficial for users who rely on the audited financial report in order to make useful economic decisions. The quality of financial information could be enhanced by providing timely information. One of the important factors that determines the timelines of the financial statement is the experience of the audit committee members, particularly, the chairman. Hence, the purpose of this study is to investigate the relationship between the industry expertise of the audit committee chairman and audit report lag. The study uses the top 100 non-financial companies listed on the Main Market of Bursa Malaysia, where the data is collected from the annual reports of those companies for the year 2018. The descriptive statistics show that the time taken by auditor to complete their audit report is about 78 days on average, with the maximum period being 122 days and the minimum being 29 days. The Ordinary Least Squares analysis reveals that industry expertise of the audit committee chairman, firm size, audit firm type, investment in internal audit and audit committee size, have a significant and negative relationship with audit report lag. While audit fees is found to be significantly and positively associated with audit report lag, there is no evidence supporting the relationship between financial condition, audit committee meeting, audit committee independence and loss with audit delay. This study may contribute to the existing literature regarding audit report lag, especially on the influence of industry expertise of the audit committee chairman on audit report lag. Moreover, this study may provide useful information for policymakers to pay more attention to the vital role of industry expertise of the audit committee chairman in improving financial reporting timeliness.